Readiness towards outcome-based education in business management programs / Sariwati Md Shariff ... [et. al] - Md Shariff, Sariwati; Ahmad, Noryati; Mohamed Esa, Mashitah; Saad, Shatina (2011)
The main objective of this study was to determine the readiness level among academics towards outcome-based education (OBE) implementation for business management degree programs in a local public institution of higher learning. The secondary objective was to determine the new students’ perceptions towards OBE implementation in the faculty in July 2010. Two different survey questionnaires using 5-point Likert scale were distributed to these two groups at the end of the semester. Findings of the study revealed that there was an average OBE awareness and compliance level among the academic staff. Based on the students’ feedback, there was weak awareness on OBE that emphasized on student-centered learning. The results were expected as this was the first phase of the OBE curriculum implementation. Implications of the study showed that there were areas for continual improvement to further promote and enhance understanding and awareness on OBE among the staff and students; as well as to enforce and strengthen OBE implementation for the coming Part Two semester in January 2011. This is particularly important so as to achieve the planned program educational objectives, program and course outcomes in the new OBE curriculum design as enforced by the university and Malaysian Qualifications Agency.